INTEGRATION OF ACADEMIC AND ISLAMIC CURRICULA IN SHAPING STUDENTS' RELIGIOUS CHARACTER AT AN INTERNATIONAL ISLAMIC BOARDING SCHOOL - Ibnu Rozak JR; Baharuddin; Moh. Padhil; Rosnaini Hashim (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2026)
The moral crisis among young people has made the integration of academic and Islamic curricula an important strategy for shaping students' religious character, especially in boarding school settings. This study aims to examine how such curricular integration is designed, implemented, and evaluated collaboratively at International Islamic Boarding School (IIBS) Al-Maahira. The study uses a qualitative approach with a case study method through interviews, observation, and documentation. The findings show that integration is carried out systemically through joint planning, learning practices that contain Islamic values, structured non-academic activities, and the school environment as a hidden curriculum. In conclusion, a holistically designed integrated curriculum makes a real contribution to the formation of students' religious character. The implications of these findings encourage the development of Islamic education curricula that are integrated conceptually and operationally in modern pesantren-based educational institutions. Keywords: curriculum integration, Islamic education, religious character, boarding school.   Abstrak Krisis moral di kalangan anak muda telah menjadikan integrasi kurikulum akademik dan Islam sebagai strategi penting untuk membentuk karakter religius siswa, terutama di lingkungan pesantren. Studi ini bertujuan untuk meneliti bagaimana integrasi kurikulum tersebut dirancang, diimplementasikan, dan dievaluasi secara kolaboratif di International Islamic Boarding School (IIBS) Al-Maahira. Studi ini menggunakan pendekatan kualitatif dengan metode studi kasus melalui wawancara, observasi, dan dokumentasi. Temuan menunjukkan bahwa integrasi dilakukan secara sistematis melalui perencanaan bersama, praktik pembelajaran yang mengandung nilai-nilai Islam, kegiatan non-akademik terstruktur, dan lingkungan sekolah sebagai kurikulum tersembunyi. Kesimpulannya, kurikulum terintegrasi yang dirancang secara holistik memberikan kontribusi nyata terhadap pembentukan karakter religius siswa. Implikasi dari temuan ini mendorong pengembangan kurikulum pendidikan Islam yang terintegrasi secara konseptual dan operasional di lembaga pendidikan berbasis pesantren modern. Kata kunci: integrasi kurikulum, pendidikan Islam, karakter religius, pesantren.